Cardiovascular Risk Estimation in Patients with Hypertension: A Cross- Sectional Study - Nyayu Nina Putri Calisanie; Santi Susanti; Linlin Lindayani (Universitas Airlangga, 2020)
Introduction: Cardiovascular disease is a disease caused by the misfunctioning of the heart and blood vessels. Atherosclerosis is the main cause of cardiovascular disease. Prevention and control of cardiovascular disease can be done with early detection through screening activities. Framingham Risk Score using Body Mass Index (FRS BMI) risk assessment is very useful and easy, which is used without using lipid indicator. This study aims to estimate the risk of cardiovascular disease on patients with hypertension with Framingham Risk Score BMI.Methods: The study used a descriptive method with cross-sectional design. The samples in this study were 130 respondents who were selected using consecutive sampling and retrieval technique by using FRS BMI application questionnaire.Results: There were 11.5% respondents in low risk of CVD, 22.7% respondents at moderate risk and 60.8% respondents in higher category of cardiovascular disease 10 years later.Conclusion: Majority of patients with hypertension showed a high risk of CVD for the next 10 years. Patients’ sex and age also play an important role to increase the risk, whereby men show a higher risk of CVD for the next ten years. The hospital management and health worker should pay more attention and educate the patient about the prevention of heart disease for the next 10 years, especially for those with high risk of CVD based on FRS BMI measurement.